2005
DOI: 10.1055/s-2004-830536
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Short-Term Glycemic Regulation with Gliclazide and Metformin on Postprandial Lipemia

Abstract: Improved glycemic regulation can lower the raised fasting and postprandial triglyceride levels which are important atherosclerotic risk factors in diabetic patients even in short-term. Since this improvement in triglyceride levels comes early, diabetic patients can be evaluated for fasting and postprandial triglyceride levels in the first month of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Most interesting perhaps was the PL inhibitory activity of the sulfonylurea drug GzD, the sulfonamide SfD and the basic drug OrP, which had not been previously reported to have such an activity. Short term use of GzD by diabetic patients was shown to improve postprandial lipemia (22), which might support our findings. More relevant, perhaps, were some recent reports which demonstrated the inhibition of the related enzyme diacylglycerol lipase by glycine sulfonamide derivatives that can be structurally related to GzD and SfD (23,24).…”
Section: Lipase Inhibitory Activitysupporting
confidence: 90%
“…Most interesting perhaps was the PL inhibitory activity of the sulfonylurea drug GzD, the sulfonamide SfD and the basic drug OrP, which had not been previously reported to have such an activity. Short term use of GzD by diabetic patients was shown to improve postprandial lipemia (22), which might support our findings. More relevant, perhaps, were some recent reports which demonstrated the inhibition of the related enzyme diacylglycerol lipase by glycine sulfonamide derivatives that can be structurally related to GzD and SfD (23,24).…”
Section: Lipase Inhibitory Activitysupporting
confidence: 90%
“…20 The result of this study reveals that a regular administration of combination drug therapy for 90 days lowered lipid concentration. There was a slightly lower incidence of hypoglycemia (2%) as compared with previous studies.…”
Section: Discussionmentioning
confidence: 69%
“…In 2018, Pangeta et al reported positive and significant associations between glycemic control and the atherogenic indices of T2DM patients (36). Various doses of MET (1000-2550 mg/ day) generate significant changes in lipid profile indicators after a maximum of 3 months of treatment in a prospective controlled clinical trial setting (37,38). In the current investigation, which mirrors the real-world clinical practice situation, no significant variations in lipid profile indicators were seen following the arrangement for MET dosage titration and treatment duration.…”
Section: Discussionmentioning
confidence: 99%